Exploring circular design competencies in undergraduate education: the case of an interdisciplinary course and industry engagement - Bayraktaroglu, Serkan; Soylu, Yasemin (Emerald Group Publishing Ltd, 2026)
PurposeThe purpose of this paper is to reveal the details of an experimental furniture design studio course aiming to integrate circular economy awareness with interdisciplinary student participation and multi-stakeholder analysis. This paper also aims to propose an assessment model related to the circular design competencies.Design/methodology/approachThis study investigates a case of an industrial design project course, in collaboration with a sustainability course engaging students from industrial design, architecture and interior architecture. The project course focused on circular furniture design for the hospitality industry as an entangled problem space, integrating spatial and product-based circularity. Thisv article critically examines the pedagogical structure of the course, utilising document analysis and a custom-designed model to assess students' circular design competencies. The paper introduces a three-pillar assessment model that consolidates 14 circular design competencies for evaluating interdisciplinary circular economy learning in hospitality-focused design education. The model comprises of site-specific and systemic adaptability, circular manufacturability and circularity in business ecosystem indices.FindingsThe research findings suggest that students are comfortable in proposing site-specific circular solutions related to product design and material upcycling/recycling. Findings also highlight the necessity of skills such as lifecycle assessment particularly for determining the manufacturability index more accurately.Originality/valueThis paper contributes to education for sustainable development discourse, offering insights for universities seeking to incorporate circular design, interdisciplinary collaboration and industry engagement into their curricula.
Keywords: Education for sustainable development; Circular economy; Circular design; Design education; Hospitality industry; Furniture design; Design pedagogy; Sustainable design competencies